Visible‐Light‐Mediated Hydroxycarbonylation of Diazonium Salts. Issue 17 (13th July 2018) - Gosset, Cyrille; Pellegrini, Sylvain; Jooris, Romain; Bousquet, Till; Pelinski, Lydie
Abstract: A visible light‐promoted catalytic photoredox hydroxycarbonylation was achieved on aryl diazonium salts whether preformed or generated in situ from the corresponding anilines. This strategy allows a straightforward access to a variety of carboxylic acids under mild conditions. Abstract :